Sustainable Fisheries Management and the Welfare of Bycaught and Entangled Cetaceans - Dolman, Sarah J.; Brakes, Philippa (Frontiers in Veterinary Science, 2018)
The incidental capture of cetaceans and other protected marine wildlife in fishing gear has significant welfare implications. Many thousands of cetaceans are bycaught in fishing gear in European waters and hundreds of thousands die globally. We can expect many more to survive, but suffer from such interactions. As marine policy focuses on ‘population level’ impact assessments and ‘sustainability’ of fishing to preserve fish populations, the impacts to the individual, and their wider social group, are often largely underestimated, despite the large numbers affected. The wide range of recorded injuries, including abrasions, cuts, bruising and broken bones, along with the potential for panic associated with forced submersion, indicate that the welfare is, individually and collectively, very poor. Commercial fishing is the last human activity targeting wildlife (fish) on a grand scale where slaughter includes incidental killing of other large sapient wildlife on such a regular basis. Here, we review the compelling evidence of the short and long term welfare impacts of bycatch, and the progress made towards implementation of measures to understand and solve this significant welfare issue. We argue that policy decisions surrounding fishing do not adequately consider cetacean bycatch, including welfare impacts. Ultimately, there are welfare issues in all bycatch situations and suffering cannot plausibly be reduced without prevention. The well documented welfare implications provide a strong argument for zero tolerance of cetacean bycatch and provide a compelling case for immediate action in fisheries where bycatch is taking place. The only way to reduce the suffering is to decrease, or ideally eliminate, the number of animals caught in fishing gear. Uncertainties around the true magnitude of bycatch should not delay management decisions, even where individual bycatch estimates are considered ‘sustainable’. Lack of monitoring of sub-lethal impacts on populations may result in flawed impact assessments. We urge that animal welfare considerations should become an integral part of management decision-making in relation to bycatch globally. Enhanced, robust and transparent management systems are urgently required for the range of fisheries within which cetacean bycatch occurs, with the aim to better document and most importantly, work towards eliminating cetacean bycatch altogether.